Using Experimental Design In Assistive Learning Technology Trials: An Experience-Based Review - Ahmad, Asmala; Pramudya Ananta, Gede; Yusof, Norzihani; Ruslan, Siti Nur Azreen; Mohd Noor, Helmi Adly; Razali, Sharifah Nadiyah (EDP Sciences, 2018)
Assistive learning technologies are products that are aimed at assisting people with disabilities in improving their learning with minimum intervention of caregivers. Their efficacy has been assessed by means of experimental research trials.An experiment is characterized by the treatments and experimental units to be used,the way treatments are assigned to units,and the responses that are measured.The treatments and experimental units require representative participants or sample.However, because of the limits of numbers of participants or sample sizes,such kinds of studies have been delicate but challenging experiences.This paper attempts to review such valuable research experiences.